METODE PENERJEMAHAN PHRASAL VERB DALAM DIALOG ANTARA PERAWAT DAN PASIEN - HERAWATI BR BUKIT (Jurnal Penelitian Kesmasy, 2020)
The reason of this research was to observe an opportunity in the topic of phrasal verbs, to reveal the translation process of phrasal verbs in the nurse and patients dialogue into Bahasa Indonesia. Phrasal verb is also frequently used in their language. This research is used to analyze the phrasal verbs translation of Nurse with patients’ dialogues. Existing data are identified according to the theory of translation procedures from Vinay and Dalbernet (2000: 84-93). There are 7 translation methods that used in this research. From the research conducted, 310 phrasal verbs were found which were translated through the Vinay and Dalbernet translation method, and the most dominant method used was modulation namely 150 phrasal verbs.